HEALTH CARE FACILITIES FOR ADOLESCENT GIRLS IN KASTURBA GANDHI BALIKA VIDALAYA (KGBV) OF ASSAM - GOGOI, SAMPREETY; GOSWAMI, UTPALA; BARUAH, JURI; DAS BORA, DEEPIKA (International Journal of Clinical and Biomedical Research, 2015)
The adolescent girls of the Kasturba Gandhi BalikaVidalaya (KGBV) need access to information and services related to nutrition, reproductive health, family planning, and general health. The girls need to be taught the ways to keep their bodies clean to avoid any type of infection. As the girls are growing faster at this periods of time than at any time after their first year of life therefore nutritious food should be provided to the girls of KGBV. Methods: The state of Assam in India was selected for the present study. Multi stage sampling design was adopted for the study. The sampling units at different stages were State, District and Kasturba Gandhi BalikaVidyalayas (KGBVs). The six districts namely Dibrugarh, Sibsagar, LakhimpurNagoan, Kamrup and Barpeta District were selected purposively for the study. To elicit information from the sample, an interview schedule was developed. The collected data was organized, coded, consolidated and tabulated by using Microsoft excel sheet and analyzed systematically. The preliminary analytical devices expressed in frequency and percentage was used to assess the health care facilities provided in KGBV. Conclusion: The study indicates that although the food staffs are regularly provided to the girls of KGBV but more nutritious foods are to be incorporated in the diet. The health check up camps is to be organized in convergence with health department in a regular interval. KEYWORDS: Health care; Facilities; Adolescent; Kasturba Gandhi Balika Vidyalayas.